Free Fatty Acid Receptor 1 Signaling Contributes to Migration, MMP-9 Activity, and Expression of IL-8 Induced by Linoleic Acid in HaCaT Cells - Manosalva, Carolina; Alarcón, Pablo; González, Karina; Soto, Jorge; Igor, Karin; Peña, Fernanda; Medina, Gustavo; Burgos, Rafael A.; Hidalgo, María A. (Frontiers in Pharmacology, 2020)
Keratinocytes and neutrophils are the main cellular components in wound healing during re-epithelization and inflammation. Free fatty acids such as linoleic acid (LA) present beneficial properties for wound healing by modulating the inflammatory response. LA is a natural ligand of free fatty acids receptor 1 (FFA1), a G protein-coupled receptor (GPCR), able to modulate inflammatory process; however, the role of FFA1 in keratinocytes and wound healing remains poorly understood. In this study, we investigated the role of FFA1 signaling in migration, matrix metalloproteinase-9 (MMP-9) activity, and IL-8 expression induced by LA in keratinocytes. We confirmed that HaCaT cells, a human keratinocyte cell line, expresses the FFA1 receptor and GW1100, a selective antagonist of FFA1, decreased LA-induced migration of HaCaT cells. Also, GW9508, a synthetic agonist of FFA1, increased migration of these cells. Furthermore, ERK1/2 and p38 MAPK inhibitors abolished the LA-induced increase in cell migration. Besides, HaCaT cells stimulated with LA or GW9508 increased the activity of MMP-9 and the expression of IL-8. GW1100 partially inhibited both responses. We further evaluated the effects of HaCaT cells conditioned media stimulated with LA or GW9508 on neutrophil chemotaxis. Conditioned media induced neutrophil chemotaxis. Furthermore, IL-8 secreted by HaCaT cells stimulated with LA or GW9508, contributed to neutrophil chemotaxis. In conclusion, LA increased migration, MMP-9 activity, and expression of IL-8 from HaCaT cells via FFA1. Hence, these results showed that the effects induced by LA in keratinocytes can be mediated through FFA1, thus explaining a possible mechanism by which this fatty acid could accelerate wound healing.